1997
DOI: 10.1089/jir.1997.17.551
|View full text |Cite
|
Sign up to set email alerts
|

In VivoEffects of Chicken Interferon-γ During Infection withEimeria

Abstract: Newly hatched chickens are highly susceptible to infection by opportunistic pathogens during the first 1 or 2 weeks of life. The use of cytokines as therapeutic agents has been studied in animal models as well as in immunosuppressed patients. This approach has become more feasible in livestock animals, in particular poultry, with the recent cloning of cytokine genes and the development of new technologies, such as live delivery vectors. We have recently cloned the gene for chicken interferon-gamma (Ch-IFN-gamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(52 citation statements)
references
References 23 publications
0
51
0
1
Order By: Relevance
“…There is a correlation between resistance to these diseases and early and higher IFN-γ production. A high level of IFN-γ production has also been shown in chicken strains that are resistant to coccidiosis [20,90,139]. These observations suggest that chicken lines with an enhanced IFN-γ response are more resistant to some viral and parasitic infections.…”
Section: Cytokinesmentioning
confidence: 76%
“…There is a correlation between resistance to these diseases and early and higher IFN-γ production. A high level of IFN-γ production has also been shown in chicken strains that are resistant to coccidiosis [20,90,139]. These observations suggest that chicken lines with an enhanced IFN-γ response are more resistant to some viral and parasitic infections.…”
Section: Cytokinesmentioning
confidence: 76%
“…Therefore, ChIFN-γ probably work for Th1 immune response as reported in mammalian model [4,15]. In chickens, IL- 12 has not yet been cloned, but the cloning of chicken IL-18, which will work synergistically with IL-12, has recently been described [18]. If IL-12 of chicken is cloned in future, it seems that co-administration of IL-12 and IL-18 will increase IFN-γ production and work for Th1 responses showing a strong adjuvant activity even in chickens.…”
Section: Discussionmentioning
confidence: 88%
“…Lowenthal et al [11] showed enhancement of antibody responses in chickens co-administered of ChIFN-γ with sheep red blood cells. Lowenthal et al [12] also reported in vivo effects of ChIFN-γ administration during infection with Eimeria. So far most reports on ChIFN-γ and disease deal with coccidiosis [9,10,25].…”
mentioning
confidence: 97%
“…These results suggest that IFN-a protected the birds directly due to its intrinsic antiviral activity; whereas IFN-g protected the birds indirectly by potentiating the host immune response. Similarly, birds administered recombinant chicken IFN-g prophylactically before a coccidial challenge were found to have an increased weight gain and decreased oocyst production (Lowenthal et al, 1997;Lillehoj & Choi, 1998). The in ovo injection of recombinant cMGF reduced mortality due to Escherichia coli in the hatcher (Johnston et al, 1995).…”
Section: Cytokines As Therapeutic Agentsmentioning
confidence: 99%